Hereditary spherocytosis: review of cases and discussion of hematologic characteristics and updated diagnostic testing - Sabharwal, Kennedy A; Simon, Michael W (Journal of Advanced Pediatrics and Child Health, 2023)
Hereditary spherocytosis is a common inherited type of hemolytic anemia that results from abnormal morphology of erythrocytes. It has a high occurrence in North Americans and northern Europeans with a prevalence of 1/2000. There is a wide range in age and symptoms at presentation with some individuals being asymptomatic and others having severe diseases requiring blood transfusions. Based on the severity of symptoms, management may vary from simple observation to frequent blood transfusions, cholecystectomy for gallstones, and splenectomy. Timely diagnosis may be critical to minimize complications. Diagnostic tests have been available with varying degrees of accuracy. However new diagnostic tests with greater specificity and sensitivity are now available for more accurate diagnosis of Hereditary Spherocytosis in individuals of all ages including newborns. Illustrative cases are presented that show the variability in presentation, symptoms, complications, and care. Information is presented updating diagnostic testing that allows earlier diagnosis of children with hereditary spherocytosis. Additionally, the hematologic findings suspicious and consistent for this diagnosis are presented, serving as a guide when testing should be initiated.